Efficient co-production of EPA and DHA by Schizochytrium sp. via regulation of the polyketide synthase pathway - Wang Ma; Mengzhen Liu; Zixu Zhang; Yingshuang Xu; Pengwei Huang; Dongsheng Guo; Xiaoman Sun; He Huang (Communications Biology, 2022)
The MetE like complex is found to be capable of regulating the PKS system to produce EPA in Schizochytrium, with its activation regulating the expression of key enzymes, improving the efficiency of DHA and EPA production.